NAXALISM AND INDIA’S INTERNAL SECURITY: CAUSES AND SOLUTIONS - R. S. Pawar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Mismanagement of forests has been an issue since the British ruled India. The British government brought laws to monopolize forest resources, which were useful for this. After 1990, when the Indian government started using the natural resources of forests, the situation worsened. This created a spark in the hearts of the people living in the forests and they contributed to the movement against the Indian government. India is the seventh largest country in the world in terms of geographical area and is spread across various states with different geographical, social, cultural, religious, linguistic and regional backgrounds. Naxalism is seen as the main threat and problem that has arisen in the internal security of India since independence. In 1967, communist organizations came together in the country to oppose the exploitation of the poor, agricultural laborers and forest dwellers, the oppression of the poor, especially agricultural laborers, by the rich landlords, the capitalist-dominated policy of the government and to bring justice to all the exploited and suffering people. This oppression carried out by the government with the help of the rich can be ended only through the armed revolution shown by Mao. This blood-stained movement started from this line of thinking. This so-called revolution, which started from Naxalwadi in West Bengal, is still going on today and has spread to many parts of the country. This movement, which started with the noble motive of communism, started to stray from its original purpose as it became armed. This movement is being carried out by collecting extortion from politicians and rich businessmen. As a result, the Naxal movement has become a major threat to India's internal security today. Objective- 1) To study the dangers of Naxalism in national security. 2) To understand the history and background of the Naxalism movement. 4) To study the causes, solutions and conclusions of the facts. Assumptions- 1. Naxalism originated in the village of Naxalbari in West Bengal in 1967. 2. Poverty, unemployment and lack of basic facilities led to the growth of Naxalism. 3. Due to the failure of administration, the influence of the government in the tribal areas remained low. 4. Naxalist groups use sophisticated weapons and guerrilla warfare. 5. Even today, Naxalism is active in some parts of Chhattisgarh, Jharkhand, Odisha and Maharashtra.